Making Sense of Emotions and Affective Investments in War: RT and the Syrian Conflict on YouTube - Chatterje-Doody, Precious N. (2019)
Within the context of an ‘affective turn’ in media studies and the social sciences, this article explores the methodological challenges of researching emotions when studying online videos of conflict. Our study focuses on videos of the Syrian conflict shared on YouTube by the Russian state funded international broadcaster, RT. We propose that the concept of affective investment is a useful pivot between online videos of conflict and audience responses to them. Our study interrogates the role that affective investments play in 1) RT’s YouTube representations of the Syrian conflict, and 2) audience comments on these videos. We draw attention to the important intersections of RT’s representations of the conflict and audiences’ affective investments in those representations, and draw attention to the methodological issues raised. Our empirical focus is two critical junctures in the Syrian conflict: the commencement of Russia’s military intervention; and following the announcement of plans to withdraw Russian troops. We conclude by discussing the utility of affective investments in war when assessing online coverage of conflict, and suggesting avenues for further development.